PENGARUH BRAND AWARENESS DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SORKA INDONESIA DI PLATFORM E-COMMERCE SHOPEE - Riska Nuraini; Dadan Abdul Aziz Mubarok; Wildan Guretno Prasetiyo (IKRAITH-EKONOMIKA, 2025)
The rapid expansion of e-commerce in Indonesia has reshaped consumer purchasing patterns, particularly in the fashion segment such as women’s bags. Sorka Indonesia is a local brand that sells its products on Shopee. However, despite its high rating, thousands of positive reviews, and significant visitor traffic, its sales performance remains suboptimal. This study aims to analyze whether purchasing decisions for Sorka Indonesia products on Shopee are influenced by brand awareness and sales promotion. The study adopts a quantitative approach incorporating descriptive and verificative analyses. A purposive sampling technique was applied to obtain data from 100 respondents, with responses collected through an online questionnaire using a Likert-scale measurement administered via Google Forms. The findings reveal that brand awareness does not have a significant effect on purchasing decisions, whereas sales promotion exerts a positive and statistically significant, although relatively modest, influence. In addition, the joint effect of brand awareness and sales promotion on purchasing decisions is statistically significant, as supported by the results of the F-test. The findings indicate that promotional activities, including discounts, vouchers, and cashback, are significant factors in encouraging consumers to purchase Sorka Indonesia products on the Shopee marketplace.